Assessment of Conventional Full-Scale Treatment for the Removal of Endocrine Disruptors and Pharmaceuticals Present in the Tibagi River (Paraná State, Brazil) - Fazolo, Ajadir; Batista, Lígia Flávia Antunes; Nonaka, Fernanda Martins; Sanson, Ananda Lima; Alves, Mariana Corrêa Pessato; Afonso, Robson José de Cássia Franco; Aquino, Sérgio Francisco de (Frontiers in Environmental Science, 2021)
The concentrations of 25 pharmaceuticals and endocrine disruptors were monitored in the water coming from the Tibagi River (State of Paraná, Brazil) and in a conventional water treatment plant (WTP) over 13 sampling campaigns. In raw water, only 3 compounds (bisphenol A, dexamethasone and losartan) were detected with high frequency (> 75%) and 4 drugs (estradiol, diclofenac, loratadine and naproxen) were found with moderate frequency (between 30% and 70%). In addition, 7 micropollutants (paracetamol, ethinylestradiol, caffeine, propanolol, diltiazem, benzafibrate and promethazine) were not detected in any of the samples analyzed and 11 other compounds were quantified at low frequency (up to 25%). The conventional treatment process employed at WTP- Jataizinho has proven to be very efficient in removing dexamethasone (~99%), moderately efficient in reducing bisphenol A (~47%) concentration and inefficient in removing losartan (~22%) and loratadine (not removed). The greatest removals were observed during the water clarification stage using aluminum sulfate as coagulant. In general, the dry and rainy seasons did not influence the concentrations of pharmaceuticals and endocrine disruptors in raw water. In terms of the 5 most prevalent micropollutants in treated water (bisphenol A, losartan, dexamethasone, loratadine and naproxen), the human health risk associated with ingesting contaminated water was assessed and considered negligible.